The Future of the Foresight Professionals: Results from a Delphi Study - Gary, Jay E.; von der Gracht, Heiko (Futures, 2015)
How will foresight practice evolve into the next decade and beyond? How might its supply and demand factors self-organize? In 2012 a real-time Delphi study, entitled, “The Certification of Professional Futurists 2030,” was conducted among 142 experts from 29 countries to debate the forces that might diminish or enhance futures work. The study consisted of 14 projections out to the year 2030, ranging from whether the global futures field might “employ a viable form of certification for professional futurists,” to whether it might “share a common accepted understanding of futures assumptions, theory, methods, knowledge, and ethics.” Panelists identified themselves with various futures associations. This article presents the findings, including where there is dissent and consensus in the futures field over the likelihood, impact and desirability of the professionalization of its practice. Further scale development using factor analysis, ordered by the theory of competitive advantage, produced a scenario model of three market forces: assimilation, academicisation, or certification. The third force of professional certification by 2030 was deemed least likely and less desirable. This wide ranging survey therefore offers the futures field a common conversation protocol to rethink how it might redesign its value chain and differentiate itself against other professions.<br